RANCANG BANGUN SISTEM GATE BARRIER MENGGUNAKAN QUICK RESPONSE CODE (QR CODE) DAN MIKROKONTROLER ESP32 - Al Kahfi, Sidratul Rezky; Tharam , Medi Yuwono; Yuniarto, wendi (Electrical Network Systems and Sources, 2025)
Parking space security has become an important aspect as technology develops which shifts manual parking systems to automatic systems. One technology that has been used is Radio Frequency Identification (RFID), but the system. this has limitations such as the risk of losing or damaging the access card. Therefore, this research proposes the use of Quick Response Code (QR Code) as an alternative to the RFID card system to increase the efficiency and convenience of parking access. This research uses an experimental method with a hardware and software system design approach. Tests were carried out to measure the distance and scanning time of the GM66 scanner and ensure that synchronization with the database was running optimally. Test results show that the GM66 scanner has an average scanning distance of 27.5 cm with a response time of 0.5 millseconds. The gate barrier relay opens the bar in 1.48 seconds and closes in 5.19 seconds. This system was developed using XAMPP and MySQL software, with C, PHP, HTML and JavaScript programming languages. The entire system was successfully tested and functions well, demonstrating high efficiency and accuracy in supporting modern parking operations. Keywords: QR Code, Parking, GM66 Scanner, Web Based Application, ESP32